Representación argumentativa del razonamiento sobre interpretaciones del conocimiento científico - Bodanza, Gustavo Adrian (2006)
Scientific explanations and predictions are made of arguments. The theories provide the premises that, under specific initial condi-tions, support the conclusions: statements describing the phenom-ena to be explained or predicted. These arguments are defeasi-ble, since one theory might elicit better arguments than another. This lead us to the idea that the process by which scientific expla-nations and predictions are justified can be studied through models of defeasible argumentation. This work introduces a simple model in which arguments conformed by structures of the form átheory, factñ interact through a defeat relation towards a final acceptance (or rejection) within the represented scientific field. Taking rela-tions like explicative strength and simplicity as implicit in the defeat relation, the model can represent the usual circumstances in sci-ence where a weakly explicative theory survives because of meth-odological advantages like simplicity.